Constitution, Non-Causal Explanation, and Demarcation - Lorenzo Casini; Michael Baumgartner (Ergo, An Open Access Journal of Philosophy)
In philosophy of science, constitutive explanations have attracted much attention since Craver’s influential book Explaining the Brain (2007). His Mutual Manipulability (MM) theory of constitution aimed to explicate constitution as a non-causal explanatory relation and to demarcate between constituents and non-constituents. But MM received decisive criticism. In response, Craver et al. (2021) have recently proposed a new theory, called Matched Interlevel Experiments (MIE), which is currently gaining traction in various fields. The authors claim that MIE retains “the spirit of MM without conceptual confusion.” Our paper argues that this claim is not borne out: neither does MIE meet MM’s objectives nor is it free of conceptual confusion. At the same time, we show that it is possible to meet MM’s objectives in a conceptually sound manner—by adopting the so-called No De-Coupling theory of constitution.